The effectiveness of different mineralizing agents in reducing dentine permeability - an in vitro study / Marwah Berkathullah Shariff - Marwah, Berkathullah Shariff (2017)
The effectiveness of different mineralizing agents in reducing dentine permeability?an In Vitro study. Objectives: To evaluate and compare the effectiveness of mineralizing agents in reducing the dentine permeability by tubule occlusion using fluid flow filtration device and SEM/EDX analysis.Seventy five (n= 75) dentine discs of 1Â±0.2 mm width were prepared from sound permanent human molars. Fifty (n=50) dentine specimens were randomly divided into five groups (n=10). Group 1: GC Tooth Mousse Plus (Reca Dent GC Corporation Tokyo, Japan), Group 2: Clinpro White Varnish (3M ESPE, USA), Group 3: Duraphat Varnish (Pharbil Waltrop GmbH, Germany), Group 4: Colgate sensitive Pro?Relief dentifrice (Colgate Palmolive, Thailand), Group 5: Biodentine (Septodont/UK). The manufacturerï¿½s instructions for the mixing and application procedures were followed accordingly. Dentine permeability was measured after Rx application at 10 minutes, and after artificial saliva immersion at 10 minutes and 7 days interval. Subsequently, all the samples were subjected to citric acid challenge for 3 minutes and the permeability measured. The quantitative measurements in the permeability were quantified using a fluid flow filtration device functioning at 100 cmH2O (1.4 psi) pressure. Three repetitive measurements at 4 minutes duration were recorded. The average permeability values were expressed as percentage of maximum hydraulic conductance. Data were analyzed by two?way repeated measures ANOVA to determine if there are any significant differences between inter and intra treatment groups. The remaining dentine specimens (n=25) were used for SEM/EDX analyses to obtain qualitative results on dentine morphology and surface deposits.Each of these five mineralizing agents significantly reduced dentine permeability immediately after treatment application at 10 minutes and created precipitates on the treated dentine surfaces which reduced the diameter of dentin tubules. All the treatment agents increased the permeability values after 10 min and 7 days artificial saliva immersion except Clinpro white varnish and Biodentine which showed a decrease in permeability for the later immersion with the treated surface exhibiting partial modification. Clinpro white varnish exhibited significant resistance to acid challenge compared to other treatment agents under both SEM/EDX analysis and dentine permeability evaluation. Clinpro white varnish and Biodentine are effective agents in reducing dentine sensitivity compared to others. The Clinpro white varnish has a supplementary effect of resisting the acid challenge.